Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2006
DOI: 10.1371/journal.pbio.0040416
|View full text |Cite
|
Sign up to set email alerts
|

Drosophila NMNAT Maintains Neural Integrity Independent of Its NAD Synthesis Activity

Abstract: Wallerian degeneration refers to a loss of the distal part of an axon after nerve injury. Wallerian degeneration slow (Wlds) mice overexpress a chimeric protein containing the NAD synthase NMNAT (nicotinamide mononucleotide adenylyltransferase 1) and exhibit a delay in axonal degeneration. Currently, conflicting evidence raises questions as to whether NMNAT is the protecting factor and whether its enzymatic activity is required for such a possible function. Importantly, the link between nmnat and axon degenera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

13
230
0
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
3
2
2

Relationship

1
6

Authors

Journals

citations
Cited by 158 publications
(244 citation statements)
references
References 60 publications
(70 reference statements)
13
230
0
1
Order By: Relevance
“…Drosophila contains only one NMNAT gene, whose overexpression delays axonal degeneration 2 . This study and our finding that NMNAT functions as a maintenance factor to protect against activity-induced neurodegeneration 1 suggest that NMNAT alone can protect against multiple neurodegenerative insults. Our recent finding that enzymatically inactive NMNAT retains neuroprotective capabilities also exposed a hitherto unknown molecular function 1 .…”
supporting
confidence: 54%
See 1 more Smart Citation
“…Drosophila contains only one NMNAT gene, whose overexpression delays axonal degeneration 2 . This study and our finding that NMNAT functions as a maintenance factor to protect against activity-induced neurodegeneration 1 suggest that NMNAT alone can protect against multiple neurodegenerative insults. Our recent finding that enzymatically inactive NMNAT retains neuroprotective capabilities also exposed a hitherto unknown molecular function 1 .…”
supporting
confidence: 54%
“…Overexpression of wild-type NMNAT or enzyme-inactive NMNAT (NMNAT-WR) 1 suppresses the degenerative phenotypes induced by overexpression of Drosophila ataxin-1 (dAtx-1). It also offers moderate protection against the severe phenotypes caused by overexpression of human ataxin-1 with an expanded (82) poly-glutamine tract (hAtx-1[82Q]) 16 (Fig.…”
mentioning
confidence: 99%
“…Such protective effects could be mimicked by exogenously provided NAD or its biosynthetic precursors such as nicotinamide or nicotinamide riboside (Araki et al, 2004;Wang et al, 2005;Sasaki et al, 2006), suggesting that Wld S /Nmnat1 may act, at least partially, through NAD biosynthesis. Similarly, independent studies also showed that Nmnat1 could protect axon degeneration in Drosophila-based in vivo models Zhai et al, 2006).…”
Section: Molecular Mechanisms Of Wld S -Mediated Protectionmentioning
confidence: 89%
“…Initially, there was some controversy regarding whether individual fragments of the Wld S gene (UFD2 or Nmnat1), or the entire chimeric gene, are responsible for the phenotypes (Araki et al, 2004;Wang et al, 2005;Zhai et al, 2006;Conforti et al, 2007). In cultured neurons, we and others found that while inhibiting the ubiquitin proteosome system activity can slow down Wallerian degeneration (Zhai et al, 2003;MacInnis and Campenot, 2005), over-expressing Nmnat1 alone could mimic the protective effects of Wld S (Araki et al, 2004;Wang et al, 2005;Sasaki et al, 2006).…”
Section: Molecular Mechanisms Of Wld S -Mediated Protectionmentioning
confidence: 98%
See 1 more Smart Citation